The association of mobility disability and obesity with risk of unemployment in two cohorts from Sweden - Mattias Norrbäck; Per Tynelius; Gerd Ahlström; Finn Rasmussen (BMC, 2019)
Abstract Background People with mobility disability (MD) or obesity often have more health problems and are less able to participate in work than individuals without these conditions. This study investigated whether people burdened with MD and obesity have a greater risk of unemployment than people with either one (MD only or obesity only) or none of these conditions. Methods The study included two Swedish population-based cohorts, a national cohort (n = 39,947) and a regional cohort (n = 40,088). Six exposure groups were created using baseline self-reported data on MD and body mass index from participants aged 19 to 64 years. The MD definition differed between the cohorts. Various sources of socio-demographic factors were used to address confounding. Participants' risks of unemployment were assessed longitudinally in a nationwide register with objective data and with almost no loss of follow-up (< 1%). Cox regression was used to analyse associations of MD and/or obesity (BMI ≥ 30) with risk of any (≥1 day) and long-term unemployment (≥90 days during two consecutive years). Quantile regression was used to estimate participants' unemployment risks as average days of unemployment. Normal-weight people without MD were used as a reference group. The Wald test was applied for specific group comparisons other than to the reference group. Results In summary, the groups with MD and the obese group without MD had a higher risk of becoming unemployed than the reference group (regional survey adjusted hazard ratio range: 1.30-1.59; 95% CI range: 1.06-1.90, national survey adjusted hazard ratio range: 1.11-1.34; 95% CI range: 0.88-1.81). The obese group with MD did not differ from the groups with MD only or obesity only in terms of unemployment risk. Conclusions People with MD and/or obesity are vulnerable groups at risk of prolonged unemployment during their working life in a country with a highly developed welfare system.